Single-cell mass cytometry on peripheral cells in Myasthenia Gravis identifies dysregulation of innate immune cells - Verdier, Julien; Fayet, Odessa-Maud; Hemery, Edouard; Truffault, Frédérique; Pinzón, Natalia; Demeret, Sophie; Behin, Anthony; Fadel, Elie; Guihaire, Julien; Corneau, Aurélien; Blanc, Catherine; Berrih-Aknin, Sonia; et al. (Frontiers in Immunology, 2023)
Myasthenia Gravis (MG) is a neurological autoimmune disease characterized by disabling muscle weaknesses due to anti-acetylcholine receptor (AChR) autoantibodies. To gain insight into immune dysregulation underlying early-onset AChR+ MG, we performed an in-depth analysis of peripheral mononuclear blood cells (PBMCs) using mass cytometry. PBMCs from 24 AChR+ MG patients without thymoma and 16 controls were stained with a panel of 37 antibodies. Using both unsupervised and supervised approaches, we observed a decrease in monocytes, for all subpopulations: classical, intermediate, and non-classical monocytes. In contrast, an increase in innate lymphoid cells 2 (ILC2s) and CD27- gδ T cells was observed. We further investigated the dysregulations affecting monocytes and gδ T cells in MG. We analyzed CD27- gδ T cells in PBMCs and thymic cells from AChR+ MG patients. We detected the increase in CD27- gδ T cells in thymic cells of MG patients suggesting that the inflammatory thymic environment might affect gδ T cell differentiation. To better understand changes that might affect monocytes, we analyzed RNA sequencing data from CD14+ PBMCs and showed a global decrease activity of monocytes in MG patients. Next, by flow cytometry, we especially confirmed the decrease affecting non-classical monocytes. In MG, as for other B-cell mediated autoimmune diseases, dysregulations are well known for adaptive immune cells, such as B and T cells. Here, using single-cell mass cytometry, we unraveled unexpected dysregulations for innate immune cells. If these cells are known to be crucial for host defense, our results demonstrated that they could also be involved in autoimmunity.